99mTc Labeled Myocardial Imaging Agents of Long-chain Fatty Acid: An Intermediate Synthesis Process Research - Huo, Qing; Xue, Jingquan; Liu, Yu (Asian Journal of Chemistry, 2013)
Myocardial fatty acid metabolic imaging agent can be used for studying the myocardial ischemia positioning, measurements reflect changes in myocardial metabolic function and the detection of myocardial cell survival, provide a reliable basis for the clinical diagnosis of cardiac disease. In this paper, we study the synthesis of fatty brominated products BSE, which is the intermediates of novel 99mTc-labeled fatty acid metabolic imaging agent. The final yield of the product was 38 %, NMR spectroscopy confirmed very consistent the hydrogen peak displacement and integral spectrum area with the goal of formula. This synthetic route is convenient, simple, economic and has a potential value of industrial applications.